Experimental Study on an Innovative Biopolymeric Treatment Against Salt Deterioration of Materials in Cultural Heritage - Bassi, Mattia; Sassoni, Enrico; Franzoni, Elisa (Frontiers in Materials, 2021)
Salt crystallization is one of the harshest deterioration mechanisms affecting heritage materials, causing impressive decay patterns and the loss of a high thickness of original materials. Although salt damage has been widely investigated in the literature from the theoretical and experimental points of view, the solutions to mitigate this problem are still extremely limited. In the present paper, a new biopolymeric treatment based on chitosan was tested on two kinds of porous limestones widely used in historic architecture, aiming at inhibiting the crystallization of sodium sulphate inside the stone and promoting the formation of salt efflorescence over the surface, rather than harmful subflorescence inside the pore network. The treatment was applied to the bare stone and also after an inorganic pre-treatment based on the formation of hydroxyapatite in the stone. Hydroxyapatite was recently proposed for the consolidation and protection of carbonate stones and here it is expected to provide an effective anchoring layer for the chitosan coating on the pores surface, and also to prevent the calcite washout from the stone and hence the removal of chitosan. The effect of hydroxyapatite alone was also tested, for comparison’s sake. Treated and untreated stone specimens were subjected to two different accelerated salt crystallization tests, one based on crystallization cycles (wetting-drying cycles) and the other one based on continuous capillary absorption of a saline solution (“wick effect”), evaluating the results in terms of weight loss, efflorescence formation, and changes in porosity and mechanical properties. The results showed that all the treatments are compatible with the stones, and the combined treatment (hydroxyapatite + chitosan) is extremely promising for the prevention of salt damage.